SECONDARY AMENORRHEA THERAPY WITH ACCUPUNCTURE AND TURMERIC - FENUGREEK HERBAL - Izzaty, Nindy Rahmi; Imandiri, Ario; Suciati, Suciati (Faculty of Vocational Studies, Universitas Airlangga, 2017)
Background: Secondary amenorrhea is a condition when period cycle of women with irregular menstruation disappeared within six months in a row or; when the period cycle of regular menstruation women disappeared during three months in a row. In Traditional Chinese Medicine (TCM), amenorrhea is known as Jing Bi. The patient in this study case was having secondary amenorrhea with menstrual complaints not within 3 months and 22 days after the last periods. Patient was classified as secondary amenorrhea with differentiation of Qi and blood deficiency syndrome. Purpose: To know the effect of acupuncture therapy with Sanyinjiao point (SP6), Taichong point (LR3), Zusanli point (ST36), Gui lai point (ST 29) combined with turmeric herbal therapy (Curcuma domestica Val) and klabet seed (Trigonella foenum-graecum L.) in patients with secondary amenorrhea. Method: Treatment of this secondary amenorrhea case was using acupuncture and herbal therapy. Acupuncture therapy at acupoint Sanyinjiao (SP6), Taichong (LR3), Zusanli (ST36), and Gui Lai (ST29) with tonification principle of Qi and blood and improve menstrual flow. The herbal therapy given were turmeric (Curcuma domestica Val) and fenugreek seeds (Trigonellafoenum-graecum L.), which has estrogenic effect. Result: Estrogen stimulates the lining of the uterus to remove the menstrual blood. In the treatment of secondary amenorrhea, acupuncture therapy was given 21 times, three times a week. Herbal therapy was given for 60 days, taken 2 times a day with dose of 15 grams of turmeric and 4 grams of fenugreek seeds. This therapy might help the menstrual blood exuviation. Conclusion: Acupuncture and herbal therapy can be applied continously to the patient up until regular period cycle are attained.